Trade Policy Reform in the East Asian Transition Economies - Martin, Will (World Bank, Washington, DC, 2014)
The performance of the East Asian transition economies in export and income growth has been strikingly better than that of countries in Eastern Europe and the former Soviet Union. The East Asian economies have achieved remarkably high growth rates in outputs and exports without the often large declines in output and exports observed in Eastern Europe and the former Soviet Union. East Asian reformers have successfully made many of the parallel changes needed in both domestic and trade policies to secure export and income growth. (It makes no sense, for example, to introduce the trade policy instruments of a market economy when the domestic economy is still based on central planning.) But there has been no single magic formula for their success. The author discusses what each of the economies (Cambodia, China, Lao People's Democratic Republic, and Vietnam) has done. China experienced an extended transition process; the transition ws much shorter in other East Asian transition economies--especially Cambodia. Several of the East Asian transition economies used accession to a regional arrangement as part of their reform strategy. China focused mainly on unilateral reforms and, more recently, reforms associated with its accession to the World Trade Organization. Most have made extensive use of policies to attract foreign investment and to mitigate the burden of protection on manufacturing exporters. Most of the remaining trade policy problems, although difficult, appear to be problems more of development than of transition.